2022
DOI: 10.1126/sciadv.ade5085
|View full text |Cite
|
Sign up to set email alerts
|

The D614G mutation redirects SARS-CoV-2 spike to lysosomes and suppresses deleterious traits of the furin cleavage site insertion mutation

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) egress occurs by lysosomal exocytosis. We show that the Spike D614G mutation enhances Spike trafficking to lysosomes, drives Spike-mediated reprogramming of lysosomes, and reduces cell surface Spike expression by ~3-fold. D614G is not a human-specific adaptation. Rather, it is an adaptation to the earlier furin cleavage site insertion (FCSI) mutation that occurred at the genesis of SARS-CoV-2. While advantageous to the virus, furin cleavage of spike … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…As a first step towards testing whether exosome display of SARS-CoV-2 spike would enhance its immunogenicity, we asked whether spike, a type-1 integral membrane protein, is normally secreted from the cell in exosomes. For these experiments, we used Tet-on 293 cell lines designed to inducibly express the original form of spike or a D614G form of spike, which we used previously to show that spike is primarily a lysosomal protein and that the D614G mutation enhances the lysosomal sorting of spike ( 24 ) (the spike D614G mutation was the first mutation in SARS-CoV-2 to show a distinct fitness advantage for the virus, is present in all variants of concern, and acts primarily to suppress the deleterious effects of the pandemic-triggering furin cleavage site, resulting in restoration of spike’s trafficking to lysosomes( 24 ) and the ‘up’ conformation of the receptor binding domain that promotes infectivity( 25, 26 )). These spike-expressing cell lines were grown in the presence of doxycycline for three days, after which we collected cell and exosome fractions, and examined them by immunoblot (IB).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a first step towards testing whether exosome display of SARS-CoV-2 spike would enhance its immunogenicity, we asked whether spike, a type-1 integral membrane protein, is normally secreted from the cell in exosomes. For these experiments, we used Tet-on 293 cell lines designed to inducibly express the original form of spike or a D614G form of spike, which we used previously to show that spike is primarily a lysosomal protein and that the D614G mutation enhances the lysosomal sorting of spike ( 24 ) (the spike D614G mutation was the first mutation in SARS-CoV-2 to show a distinct fitness advantage for the virus, is present in all variants of concern, and acts primarily to suppress the deleterious effects of the pandemic-triggering furin cleavage site, resulting in restoration of spike’s trafficking to lysosomes( 24 ) and the ‘up’ conformation of the receptor binding domain that promotes infectivity( 25, 26 )). These spike-expressing cell lines were grown in the presence of doxycycline for three days, after which we collected cell and exosome fractions, and examined them by immunoblot (IB).…”
Section: Resultsmentioning
confidence: 99%
“…Spike’s sorting to lysosomes is atypical, as it’s not mediated by a canonical lysosomal sorting signal in its C-terminal tail, but rather, by ill-defined structural information in the spike extracellular domain (ECD)( 24 ). Moreover, we’ve found that structure-altering mutations in spike’s ECD can interfere with spike’s trafficking to lysosomes( 24 ), leading us to ask whether the structure-altering diproline (2P) substitution (986KV987-to-986PP987)( 30, 31 ) might inhibit the lysosomal sorting of spike, as inhibition of a protein’s lysosomal sorting almost always results in its delivery to the cell surface( 32 ). Furthermore, since retention of spike in the endoplasmic reticulum (ER) is also likely to inhibit spike’s plasma membrane accumulation, we also deleted the ER retrieval signal present in its short cytoplasmic, carboxy-terminal tail( 33, 34 ), replaced it with an ER export signal( 35, 36 ), and combined these…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For these experiments, we test whether we can detect the presence of a specific oligonucleotide related to the D614G mutation (aspartic acid swapped for glycine at amino acid residue 614 on the spike protein) in the SARS-CoV-2 virus. The D614G modification was an early mutation that greatly increased the virulence of SARS-CoV-2, , and by focusing on this coding sequence with a known point mutation difference between the wild type (WT) (GAT codon) and the variant (GGT codon), we can examine the specificity of this detection approach and its resilience when challenged with potentially interfering targets.…”
Section: Resultsmentioning
confidence: 99%